The Effect Of Human Resource Quality And Work Conflict On Work Performance In Competency Mediation At Bank Indonesia Representative Office, North Sumatra Province - Wim Pranata; Mesra B (International Journal of Management, Economic and Accounting, 2024)
The type of research used in this study is a type of quantitative research, the location of the research at the Bank Indonesia Representative Office of North Sumatra Province is precisely on Jalan Balai Kota no 4 Kota Medan, the population of the research used is all employees in the Representative Office of Bank Indonesia North Sumatra Province as many as 70 employees, The sample to be used is all the population in the Representative Office of Bank Indonesia North Sumatra Province as many as 70 employees, The data collection technique used is a questionnaire, the research calculation tool is the PLS smart application version 3. The results of this study are as follows: Competence has a positive and significant effect on Work Achievement with a value of 0.384 and a significant 0.000 Work Conflict has a negative and significant effect on Competency with a value of -0.289 with a significant 0.004. Work Conflict had a negative and significant effect on Work Achievement with a value of -0.278 and a significant 0.009. The quality of human resources has a positive and significant effect on Competence with a value of 0.622 and a significance of 0.000. The quality of human resources has a positive and significant effect on Work Achievement with a value of 0.306 and a significant 0.005. Role Conflict has a negative and significant effect on Work Performance through Competency with a value of -0.111 and a significant value of 0.016. The quality of human resources has a positive and significant effect on Work Performance through Competency with a value of 0.239 and a significant 0.000.